2013
DOI: 10.1140/epjst/e2013-01735-1
|View full text |Cite
|
Sign up to set email alerts
|

Induced long-time correlations in a two-component lattice gas

Abstract: The distinguishability of at least two species of particles in the classical lattice gas with no interactions except hard-core exclusion entails additional interparticle correlations. A nonlinear mixing flow appears and manifests itself most pronounced in the case of significant difference between mobilities of species. It may result in the induced correlations for the slow component mediated by the fast one. In the quasi-one-dimensional case, the long-time correlations are demonstrated to take place in the sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Even such a short-range interaction results in a number of unexpected kinetic effects, e.g., the "back correlations" effect [36], drifting spatial structures [37][38][39], effects of "negative" mass transport [40][41][42], induced long-time correlations [43], and the dissipative pairing effect for tracers passing through a lattice gas [44]. Increasing of gas concentration (bath fraction) leads to enhancement of the role of interaction between gas particles.…”
Section: Introductionmentioning
confidence: 99%
“…Even such a short-range interaction results in a number of unexpected kinetic effects, e.g., the "back correlations" effect [36], drifting spatial structures [37][38][39], effects of "negative" mass transport [40][41][42], induced long-time correlations [43], and the dissipative pairing effect for tracers passing through a lattice gas [44]. Increasing of gas concentration (bath fraction) leads to enhancement of the role of interaction between gas particles.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, it was shown that a large enough BI generates a stress sufficient to produce defects, which remain localized near the BI and affect the frictional drag force. The microstructural changes of the medium not only enhance the drag force exerted on the BI, but also induce effective interactions between the BIs, when more than one BI is present [7]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…( 2) is a reduced nonlinear mixing flow which describes mutual drag of one component by another and arises as a result of the particle distinguishability and the local repulsion (due to excluded volume constraint) in a lattice gas [18]. This flow leads to the array of anomalous diffusive transport effects, e.g., the drag effect, formation of the drifting spatial structures [15][16][17], effects of "negative" mass transport [18][19][20], and induced long-time correlations [28].…”
Section: Trace Inversion In the Lattice Gas Modelmentioning
confidence: 99%